Guilt-proneness is associated with the use of protective behavioral strategies during episodes of alcohol use. (April 2018) - Treeby, Matt S.; Rice, Simon M.; Cocker, Fiona; Peacock, Amy; Bruno, Raimondo
Abstract: Introduction: Shame and guilt are closely related emotions with diverging implications for the development, and potential treatment, of substance use disorders. Accumulating research indicates that a guilt-prone affect style buffers individuals against the development of problematic alcohol use, while shame-proneness appears to offer no protective function. However, little is known about the manner in which guilt-prone individuals avoid the experience of alcohol use-related harms. The present study aimed to extend the shame, guilt, and substance use literature by examining whether these two self-conscious affect styles are differentially related to the use of protective behavioral strategies which reduce the risk of harms during drinking episodes. Methods: Participants ( N = 281; female n = 207) completed pen-and-paper measures of shame and guilt-proneness, level of alcohol use, and the habitual use of protective behavioral strategies during drinking episodes. Part-correlation analysis isolated shame-free guilt and guilt-free shame residuals in exploring relationships between self-conscious affect style and the use of protective behavioral strategies during drinking episodes. Results: Guilt-proneness was consistently associated with the routine use of protective behavioral strategies during episodes of alcohol intake. In contrast, shame-proneness was unrelated to the use of such protective and harm avoidance strategies when drinking. Conclusion: Findings provide additional support for the argument that guilt and shame need to be considered separately in both research and substance use treatment settings. Highlights: Guilt-proneness may buffer individuals against developing disordered alcohol use. Guilt-proneness was associated with the use of protective behaviors while drinking. In contrast, shame-proneness was unrelated to the use of protective behaviors. Interventions could shift individuals from a shame to a guilt-prone affect style.